(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
The exploitation of ground water deposits for the purposes of water-supplying has certain restrictions connected with the quantity of the exploited resources and their hydrogeological conditions. Inadmissible large amount of draw-off can bring to their exhaustion in the course of time with appropriate negative geoecological consequences. As an example some deposits of RA have been observed where large draw-off with borehole groups are carried out.